Strategi Manajemen Perubahan Dalam Meningkatkan Kinerja Organisasi - Cecep Ridwan; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Change is an inevitability in a dynamic organizational environment. Organizations that are able to survive and grow are those that can manage change effectively and strategically. This study aims to explore change management strategies that contribute to improving organizational performance. The main focus of this study includes identifying key success factors for change, the role of leadership, and the involvement of all organizational elements in the transition process. The methodology used is a qualitative approach through literature review and analysis of various change management models that have been applied in organizational practice. The findings show that well-planned and structured change management strategies can have a positive impact on organizational performance, in terms of efficiency, productivity, and employee satisfaction. Effective strategies involve open communication, continuous training, regular evaluations, and leadership that provides direction and motivation. Therefore, organizations need to adopt adaptive and sustainable change management approaches to ensure the success of transformation and the achievement of long-term goals.